Genome editing of the disease susceptibility gene CsLOB1 in citrus confers resistance to citrus canker. Issue 7 (4th January 2017) - Jia, Hongge; Zhang, Yunzeng; Orbović, Vladimir; Xu, Jin; White, Frank F.; Jones, Jeffrey B.; Wang, Nian
Abstract: Citrus is a highly valued tree crop worldwide, while, at the same time, citrus production faces many biotic challenges, including bacterial canker and Huanglongbing (HLB). Breeding for disease‐resistant varieties is the most efficient and sustainable approach to control plant diseases. Traditional breeding of citrus varieties is challenging due to multiple limitations, including polyploidy, polyembryony, extended juvenility and long crossing cycles. Targeted genome editing technology has the potential to shorten varietal development for some traits, including disease resistance. Here, we used CRISPR/Cas9/sgRNA technology to modify the canker susceptibility gene CsLOB1 in Duncan grapefruit. Six independent lines, DLOB 2, DLOB 3, DLOB 9, DLOB 10, DLOB 11 and DLOB 12, were generated. Targeted next‐generation sequencing of the six lines showed the mutation rate was 31.58%, 23.80%, 89.36%, 88.79%, 46.91% and 51.12% for DLOB 2, DLOB 3, DLOB 9, DLOB 10, DLOB 11 and DLOB 12, respectively, of the cells in each line. DLOB 2 and DLOB 3 showed canker symptoms similar to wild‐type grapefruit, when inoculated with the pathogen Xanthomonas citri subsp. citri (Xcc). No canker symptoms were observed on DLOB 9, DLOB 10, DLOB 11 and DLOB 12 at 4 days postinoculation (DPI) with Xcc. Pustules caused by Xcc were observed on DLOB 9, DLOB 10, DLOB 11 and DLOB 12 in later stages, which were much reduced compared to that on wild‐type grapefruit. The pustules on DLOB 9 and DLOB 10 did not develop into typical canker symptoms. No side effects and off‐target mutations were detected in the mutated plants. This study indicates that genome editing using CRISPR technology will provide a promising pathway to generate disease‐resistant citrus varieties.